Survey data on digitalization of building procurement process by architectural firms in Abuja, Nigeria - Eziyi O. Ibem; Adedotun O. Akinola; Emokpae M. Erebor; Morolaoluwa O. Tolani; Adaeze E. Nwa-uwa (Data in Brief, 2018)
This data article describes the dataset on the digital technologies and applications used by architectural firms in the delivery of building projects. The data set was sourced through a questionnaire survey of 75 registered architectural firms in Abuja, Nigeria. The survey was conducted between December 2017 and January 2018 in the study area. The data, which were analyzed using descriptive statistics, contain the characteristics of architectural firms in Abuja that participated in the survey, the different stand-alone and integrated data acquisition, creation, processing, storage and communication/exchange technologies, applications and tools and intelligent systems the firms use in building procurement process. In addition, the advantages and challenges associated with the use of digital technologies in the procurement of building projects by architectural firms in the study area are also presented in this dataset. Keywords: Digital technologies, Building procurement, Architectural firms, Survey, Abuja